FUNGSI MAKROPRUDENSIAL BANK INDONESIA TERHADAP BANK SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 21 TAHUN 2011 TENTANG OTORITAS JASA KEUANGAN - Mirza, Farrah Rizky Amelia (Faculty of Law, University of Palembang, 2021)
Macroprudential supervision and regulation in strengthening the function and active role of Bank Indonesia as a systemic regulator in maintaining financial system will be greatly assisted by the existence of Financial Services Authority (OJK). In OJK assist Bank Indonesia to conduct moral suasion to banking. This study discusses Bank Indonesia’s macroprudential function against banks, their limits of scope, and functional relationship between Bank Indonesia and OJK after the enactment of Law Number 21 of 2011 on OJK. It is expected that the arrangement of cooperation or coordination between the two institutions will be clearly illustrated. The method used in this study is normative law with legislative, conceptual, and historical approaches. The types and source of legal materials include primary, secondary, and tertiary legal materials. The technique used for drawing conclusions is deductive thinking, the way of thinking in which general statements are drawn into specific conclusions to obtain answers to the problems to be discussed in this journal. The study results showed that the limit of scope of macroprudential supervision/authority of BI after the coming into effect of the Law were macroprudential regulation and supervision. Macroprudential supervisory function of BI prior to the existence of OJK was to establish and implement monetary policy, regulate and maintain a smooth banking system, regulate and supervise banking activities. Macroprudential supervisory function of BI following the enactment of the Law is limited to having only a monetary policy role, maintaining rupiah stability. BI and OJK have functional relationship on macroprudential and microprudential supervision after the enactment of the law, cooperation and coordination in the implementation of their tasks according to their respective authorities, information exchange of Financial Services Institutions, and management of reporting system of banks and finance companies by BI and OJK.